THE INFLUENCE OF CUSTOMER SATISFACTION AND TRUST ON E-WOM COMMITMENT AS AN INTERVENING VARIABLE TO INCREASE STUDENTS' ONLINE SHOPPING INTEREST: PENGARUH KEPUASAN PELANGGAN DAN KEPERCAYAAN TERHADAP E-WOM COMMITMENT SEBAGAI VARIABEL INTERVENING UNTUK MENINGKATKAN MINAT BELANJA MAHASISWA SECARA ONLINE - Nandiva, Alya (LPPM UPMI, 2023)
This study aims to determine whether online shopping interest can be influenced by customer satisfaction through e-wom commitment to Management Economics students and FKIP English education at the Indonesian Community Development University Medan. This study analyzes 1.) The effect of customers on e-wom commitment 2.) The effect of trust on e-wom commitment 3.) The effect of customers on online shopping interest 4.) The effect of trust on online shopping interest 5.) The effect of e-Wom commitment on interest in online shopping. This type of research is quantitative research. The population in this study was Economics Management students and FKIP English education at the Indonesian Community Development University (UPMI) Medan who used Shopee's online shop. This research technique is Cluster Random Sampling with 58 Consumers as Respondents. This study uses an online questionnaire as a data collection instrument. This study analyzes data using SPSS version 21. The results show 1.) Customers have a significant effect on e-WOM 2.) Trust has a significant effect on e-WOM 3.) Customers have a significant effect on Interest online shopping 4.) Trust has a significant effect on online shopping interest 5.) E-wom has a significant effect on online shopping interest.